A COMPREHENSIVE GRAMMATICAL ANALYSIS OF THE ENGLISH LANGUAGE: STRUCTURE, FUNCTIONS, AND MODERN LINGUISTIC PARADIGMS - Tojiyeva Marxabo Akbarovna (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract This article provides a thorough grammatical analysis of the English language, examining its unique morphosyntactic structures, tense-aspect systems, and the functional role of grammar in meaningful communication. It highlights the transition of English from a highly inflected Germanic language to an analytical one, emphasizing the reliance on word order (Subject-Verb-Object) and auxiliary verbs. The study explores the complexities of English syntax, semantic nuances of tense forms, and contemporary challenges in linguistic analysis. This comprehensive overview aims to enhance pedagogical approaches and deepen structural understanding for advanced learners and educators.